Proteasomal System Related Stress Response in Different Cancer Cell Lines - YILMAZ, BETÜL (MARMARA UNIV, INST HEALTH SCIENCES, 2020)
Objective: Proteasomal system is the primary protein degradation mechanism and important for cellular homeostasis. On the other hand, increased proteasome activity protects cancer cells from cell death. The objective of this preliminary study was to determine the response of the proteasomal system to oxidative stress in human cancer cell lines including K562 chronic myelogenous leukemia, U251 glioblastoma, DU145 prostate cancer, HepG2C3A hepatoma, and MCF7 breast cancer. Methods: Cells were exposed to hydrogen peroxide (H2O2) as a stressor. 20S and 26S proteasome activities and K48-linked protein ubiquitination levels were determined immediately and 3 hours after exposure. Results: As an immediate response, 20S proteasome activities decreased in only K562 and U251 cells and 20S+26S proteasome activities decreased only in K562 cells. Following 3h of incubation, all cells showed a significant decrease in both 20S and 20S+26S proteasome activities. K48-linked protein ubiquitination levels increased immediately in K562 and DU145 cells. After 3h of incubation, ubiquitination levels increased in all cell lines except MCF7 cells. Conclusion: The difference in the response of the proteasomal system to stress could be the reason for differential adaptation to oxidative stress in different cancer types.
Keywords: Proteasome activity; 20S proteasome; 26S proteasome; oxidative stress; cancer